362. Performance evaluation of an orthopaedic dedicated, novel cone-beam CT scanner. (December 2018) - Zagni, F.; Durante, S.; Pierotti, L.; Sampaio, C.; Vichi, S.; Marengo, M.
Abstract : Purpose: A new conception CBCT scanner optimized of imaging of extremities in a phyisological, comfortable position (Carestream Health Onsight Extremity) has been tested at the Istituto Ortopedico Rizzoli in Bologna. We report on initial assessment of the performance as regards imaging, dose to patients and workers' radiation protection. Methods and materials: The field of view is suited to cover the whole anatomy of interest (∼25 cm in length) and data is acquired with a single rotation (a "fan angle" – 216.5 degrees). Uniformity, noise, voxel values, MTF and geometrical precision were evaluated for the most frequent clinical protocol (90 kV, 5 mA, total scan time 25 s), using the dedicated phantom provided by the manufacturer. In the lack of a standardized method, dose measurements were practically measured with the standard 10-mm pencil chamber dedicated to conventional MDCT scanners. Using the standard CT head-phantom we evaluated two "weighted CTDI-like" values by locating the chamber at the axial centre and in a head-to-head setup (i.e. at −5 cm and + 5 cm) thus covering 20 cm of the axial field-of-view. Dose profile in axial-direction using a point-like chamber was also evaluated in air using a "point-like" chamber. Moreover, HVL and beam quality were tested, as well as ambient dose measurements were performed. Results: Uniformity and noise gave 4.8HU (maximum difference) and 47HU (standard deviation) respectively. MTF resulted in 4.2 lp/mm @50% and 8.0 @10%. CDTI resulted in 5.8 mGy (single measurement) and 4.9 mGy (head-to-head measurement), corresponding to a normalized DLP of 4.1 mGy*cm/mAs. Incident ambient dose at the operator position was <0.05 μSv per scan. Conclusion: High quality imaging of extremities in physiological position is possible, using a dedicate CBCT scanner. Performance is comparable or better to a standard MDCT scanner, while granting low dose to patient and safe operation of the staff.